Striker - Michael Hurley (Oxford, United Kingdom Capstone Global Library Ltd, 2010)
Alongside biographies of famous international players at each of these positions, Football Files looks at fitness, techniques, and nutrition. This high interest recreational read will engage readers by looking at the history and skills of some of their favourite players, whilst giving them great tips on how to play like their heroes.
Keywords: Non-Fiction -- Non-Fiction